PERANCANGAN INTERIOR HOTEL RESORT PANTAI KLAYAR DI PACITAN - Yusuf Kurniawan; Indarto Indarto (Pendhapa, 2018)
ABSTRACTPacitan has a chance is prospective to be developed into tourism industry and tourism to compete with other regions and even abroad. Tourism potential include shore excursions, cave tours, cultural tourism, religious tourism, recreational tourism and travel industry. Pacitan known natural attractions beautiful beaches and charming, one of which is Turkish Klayar, beach has natural charms of the exotic with great views and beautiful natural scenery. Turkish Klayar potential and started to be developed into a tourism destination in Pacitan, because it can make the higher tourist visits, visits of tourist every year the statistics are significant surge. And so we need adequate accommodation such as Hotel Resort considering the number of tourists who come to vacation, this time Klayar Beach travel area there are only a kind of homestay accommodation is still minimal infrastructure facilities. Interior Design Resort Beach Hotel Klayar carries natural style ethnic with ethnic concept for the future should be able to show the identity of Pacitan condensed Javanese cultural traditions that are owned. Featuring designs that are ethnically not display the old-fashioned design, but the design is constantly evolving and is able to keep abreast of the times. Keyword: Interior, Klayar, Pacitan, Design, Resort